Using technology acceptance model to investigate digital business intention among Indonesian students - Agus Wibowo; Ari Saptono; Bagus Shandy Narmaditya; Mohammad Sofwan Effendi; Saparuddin Mukhtar; Suparno; Muhammad Hakimi Mohd Shafiai (Cogent Business & Management, 2024)
The digitalization of entrepreneurship articulates concepts from various streams of literature to promote entrepreneurial intentions. This study investigates the influence of digital entrepreneurship education, perceived usefulness, and perceived ease of use on digital entrepreneurial intentions. Drawing on knowledge-based literature, this research explores the mediating effect of digital entrepreneurial self-efficacy. The data were collected from 309 university students in Indonesia through a self-administered survey, and the hypotheses were estimated using PLS-SEM with Smart-PLS 3.0. The findings indicate that digital entrepreneurship education significantly affects digital entrepreneurial self-efficacy and intention among Indonesian students. This study also demonstrates that the variables of the technology acceptance model can promote digital entrepreneurial self-efficacy and intention. In addition, the result confirms the mediating role of digital entrepreneurial self-efficacy in explaining the association between digital entrepreneurship education, perceived ease of use, and entrepreneurial intentions.
Keywords: 650; Digital entrepreneurial intention; digital entrepreneurship education; perceived usefulness; perceived ease of use; digital entrepreneurial self-efficacy